Beyond the procedure: A call for precision in diagnosis, risk mitigation, and sustainability of endovascular intervention in peripheral artery disease - Kurnianingsih, Novi (Heart Science Journal, 2025)
Endovascular interventions have made a lot of advancements in managing peripheral arterial disease (PAD). The interventions of PAD were limited only to medical therapy or surgery, but as for now, it has undergone changes because of improvements in the tools used for intervention and the improved operator skill, so the patients are able to gain benefits, even if the intervention is minimally invasive. The benefit does not stop at the technical success; it extends to the precision in diagnosing, extensive risk mitigation, and sustainable outcomes. Duplex ultrasonography is now popularly used because of its ease of use, following more advanced examinations such as CT or MR angiography, resulting in accurate, on-time, and precise interventions. But, there are several challenges left, such as the low rate of use of guideline-directed medical therapy that may lead to an increased number of mortality and amputation risk. Furthermore, multidisciplinary collaboration is deemed essential in optimizing sustainability. Patency or angiography, which are usually used as parameters traditionally, are not enough to measure the success of the therapy; instead, limbs preserved, improvement of the function, and the quality of life may define success in therapy, where endovascular interventions may directly affect those parameters mentioned. In order to achieve sustainable and meaningful outcomes affecting the long-term well-being of patients, patient-centered strategies, early detection, and maximizing the use of resources are a must.